Geological, geochemical, and geophysical survey of the geothermal resources at Hot Springs Bay Valley, Akutan Island, Alaska - Motyka, R. J.; Wescott, E. M.; Turner, D. L.; Swanson, S. E.; Romick, J. D.; Moorman, M. A.; Poreda, R. J.; Witte, W.; Petzinger, B.; Allely, R. D.; Larsen, M. (Alaska. Division of Geological and Geophysical Surveys., 1985)
An extensive survey was conducted of the geothermal resource potential of Hot Springs Bay Valley on Akutan Island. A topographic base map was constructed, geologic mapping, geophysical and geochemical surveys were conducted, and the thermal waters and fumarolic gases were analyzed for major and minor element species and stable isotope composition. (ACR)